Nutrição mineral e escleromorfismo foliar de grupos funcionais e comunidades vegetais savânicas - Souza, Marcelo Claro de [UNESP] (2014)
Savannas (located in Australia, Brazil and South Africa) hold the second largest biodiversity on the planet. These savannas have developed their vegetation structure on acidic and nutrient-poor soils, under a well-defined dry and rainy seasons. Among the limiting ecological filters, fire, soil fertility, water availability and herbivory are considered the most important ones. Other filters, which may be considered subfilters of the soil fertility are acidity and aluminum (Al) availability in the soil. Aluminum is considered a toxic element for most plant species, however savanna plants are insensitive to Al, and some species are Al-accumulators. We studied leaf nutritional status, Al accumulation and leaf scleromorphism of savanna species at three levels: regional, national and intercontinental. For national and intercontinental analysis we evaluated variations in the annual 9 rainfall, soil fertility and soil acidity. At the regional level, we compared leaf scleromorphism, nutritional status, Al accumulation, leaf phenology and the concentration of secondary metabolites in young and mature leaves of Al-accumulator and non-accumulator species in a cerrado remnant in Itirapina-SP. At the national level we compared the nutritional status, Al accumulation and leaf scleromorphism variations between two cerrado sensu stricto (s. str.) fragments:, one in the core region (Brasília - DF) and another on the southeastern periphery of the cerrado (Itirapina - SP). On a global scale, we studied the dissimilarities on the nutritional status, Al accumulation and leaf scleromorphism between the Australian, Brazilian and South African savannas. At the regional level, we observed two distinct strategies of leaf development between Al-accumulator and non-accumulator species. At the national level, we concluded that the peripheral cerrado community was less scleromorphic than the community in the core. These variations were explained by the higher soil...